2014
DOI: 10.1016/j.chom.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Transmission Bottlenecks Are Defined by Infection Route and Recipient Host

Abstract: SUMMARY Despite its global relevance, our understanding of how influenza A virus transmission impacts the overall population dynamics of this RNA virus remains incomplete. To define this dynamic, we inserted neutral barcodes into the influenza A virus genome to generate a population of viruses that can be individually tracked during transmission events. We find that physiological bottlenecks differ dramatically based on the infection route and level of adaptation required for efficient replication. Strong gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
236
2
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(258 citation statements)
references
References 38 publications
17
236
2
3
Order By: Relevance
“…The virus was amplified on Madin-Darby canine kidney (MDCK) epithelial cells as described elsewhere (33)(34)(35). Virus infection and titration studies were performed as described previously (33,(36)(37)(38).…”
Section: Virus and Cellsmentioning
confidence: 99%
“…The virus was amplified on Madin-Darby canine kidney (MDCK) epithelial cells as described elsewhere (33)(34)(35). Virus infection and titration studies were performed as described previously (33,(36)(37)(38).…”
Section: Virus and Cellsmentioning
confidence: 99%
“…Intranasal inoculation of ferrets with a liquid inoculum does not reflect the capacity for natural virus infection by contact or the airborne route; the increasing use of aerobiology in recent years has enabled the modeling of more complex modes of virus transmission which are relevant to our understanding of the true capacity of an influenza virus to cause disease in mammals. Prior studies from our laboratory and others have found that ferrets are susceptible to infection with low doses of aerosolized influenza virus, often displaying symptoms more comparable to those occurring during natural human infection (19,20). To determine if aerosol administration of NY/108 virus would alter its virulence in ferrets compared to that after i.n.…”
mentioning
confidence: 98%
“…A ferret model of household contact was developed by using a directly inoculated ferret to transmit virus to susceptible contacts and then using these contact ferrets to test the efficacy of prophylactic regimens (32); while this approach yields ferrets that are more "naturally" infected, potentially augmenting the applicability of the results to human situations, it is difficult to control precisely the timing and viral input leading to infection in these contacts, increasing variability in the experimental protocol. As discussed in more detail below, ferrets infected "naturally" can still possess differences in virus diversity based on the transmission mode employed (33).…”
Section: Inoculation Routementioning
confidence: 99%
“…In other words, the naive ferret shares no common housing spaces with the inoculated ferret, ensuring that if the contact ferret becomes infected, the source must have been respiratory droplets originating from the inoculated ferret (RD model). This model represents a far more stringent evaluation of virus transmissibility, as many viruses that demonstrate the capacity for transmission when ferrets are placed in direct contact are not transmitted by the respiratory droplet or aerosol route (64,65), potentially due to differences in bottleneck stringency between different routes of transmission (33). For both models, transmission is typically assessed by the detection of both infectious virus in contact ferrets during the experimental period and evidence of seroconversion to homologous virus during the convalescent phase of infection (38).…”
Section: Transmission Modelsmentioning
confidence: 99%